Long-Term Leisure-Time Physical Activity Intensity and All-Cause and Cause-Specific Mortality: A Prospective Cohort of Us Adults - De Moraes-Ferrari, G (Lippincott Williams and Wilkins, 2022)
Background: The 2018 physical activity guidelines for Americans recommend a minimum of 150 to 300 min/wk of moderate physical activity (MPA), 75 to 150 min/wk of vigorous physical activity (VPA), or an equivalent combination of both. However, it remains unclear whether higher levels of long-term VPA and MPA are, independently and jointly, associated with lower mortality. Methods: A total of 116 221 adults from 2 large prospective US cohorts (Nurses Health Study and Health Professionals Follow-up Study, 1988-2018) were analyzed. Detailed self-reported leisure-time physical activity was assessed with a validated questionnaire, repeated up to 15 times during the follow-up. Cox regression was used to estimate the hazard ratio and 95% CI of the association between long-term leisure-time physical activity intensity and all-cause and cause-specific mortality. Results: During 30 years of follow-up, we identified 47 596 deaths. In analyses mutually adjusted for MPA and VPA, hazard ratios comparing individuals meeting the long-term leisure-time VPA guideline (75-149 min/wk) versus no VPA were 0.81 (95% CI, 0.76-0.87) for all-cause mortality, 0.69 (95% CI, 0.60-0.78) for cardiovascular disease (CVD) mortality, and 0.85 (95% CI, 0.79-0.92) for non-CVD mortality. Meeting the long-term leisure-time MPA guideline (150-299 min/wk) was similarly associated with lower mortality: 19% to 25% lower risk of all-cause, CVD, and non-CVD mortality. Compared with those meeting the long-term leisure-time physical activity guidelines, participants who reported 2 to 4 times above the recommended minimum of long-term leisure-time VPA (150-299 min/wk) or MPA (300-599 min/wk) showed 2% to 4% and 3% to 13% lower mortality, respectively. Higher levels of either long-term leisure-time VPA (≥300 min/wk) or MPA (≥600 min/wk) did not clearly show further lower all-cause, CVD, and non-CVD mortality or harm. In joint analyses, for individuals who reported <300 min/wk of long-term leisure-time MPA, additional leisure-time VPA was associated with lower mortality; however, among those who reported ≥300 min/wk of long-term leisure-time MPA, additional leisure-time VPA did not appear to be associated with lower mortality beyond MPA. Conclusions: The nearly maximum association with lower mortality was achieved by performing ≈150 to 300 min/wk of long-term leisure-time VPA, 300 to 600 min/wk of long-term leisure-time MPA, or an equivalent combination of both. © 2022 Lippincott Williams and Wilkins. All rights reserved.